Analisis Perbandingan Perkembangan Penyakit Bercah Daun (Cercospora capsici) pada Tanaman Cabai Merah (Capsicum annuum L) di Dataran Tinggi dan Dataran Rendah selama Musim Hujan Studi Kasus di Kabupaten Karo dan Deli Serdang - Lilis Handayani Berutu; Ahmad Rafiqi Tantawi; Dwika Karima Wardani (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
This study aims to analyze the comparison of the development of leaf spot disease (Cercospora capsici) in red chili plants (Capsicum annuum L.) in highland and lowland areas during the rainy season. Leaf spot disease is a serious problem that hinders proper growth in chili plants. The research was conducted in December 2022 using a descriptive survey method, focusing on the issue of leaf spot disease in chili plants in farmers' fields. The results showed that the average percentage of symptomatic chili plants affected by leaf spot disease in the highland area was 50.89%, while in the lowland area, it was 29.77%. The average level of leaf spot disease incidence in the highland was 26.79%, whereas in the lowland, it was 24.61%. From these findings, it can be concluded that leaf spot disease (Cercospora capsici) has a higher incidence rate in red chili plants in the highland compared to the lowland during the rainy season. Knowledge of this difference can assist farmers in taking appropriate preventive or intervention measures to address disease outbreaks in red chili plants in both regions.